Small RNA, Cyclic-di-GMP and Phenolic Compounds Regulate the Type III Secretion System in Bacterial Phytopathogens - (:unkn) unknown (My University, 2014)
Type III Secretion System (T3SS) is an essential virulence factor in many Gram-negative bacterial pathogens. Expression of T3SS consumes large amount of energy. Hence it is tightly regulated by bacteria through several mechanisms. In this work we screened a library of phenolic compounds and found several compounds that dramatically downregulate T3SS in Erwinia amylovora 273. Additionally, the role of small RNA (sRNA) chaperone, Hfq, and a secondary messenger, cyclic-di-GMP in T3SS regulation in Dickeya dadantii 3937 was also examined. Chapter 1 provides a brief overview of the history and virulence mechanisms of two phytopathogens - Erwinia amylovora 273 and Dickeya dadantii 3937. In chapter 2, a chemical library of phenolic compounds was screened. Several compounds inhibited expression of T3SS in E. amylovora 273. trans-4-methoxy cinnamic acid (TMCA) and Benzoic acid (BA) inhibited T3SS expression through HrpS-HrpL pathway. Additionally, TMCA altered T3SS expression through the rsmBEa-RsmAEa system. Additionally, trans-2-(4-hydroxyphenyl)-ethenylsulfonate (EHPES) induced T3SS expression. Finally, TMCA and BA inhibited the hypersensitive response (HR) by inhibiting expression of T3SS. In chapter 3, we investigated the role of a second messenger, cyclic-di-GMP in the regulation of T3SS expression in D. dadantii 3937. A PilZ domain protein, YcgR regulated expression of T3SS in a c-di-GMP-dependent manner. A point mutation was created by replacing the crucial arginine residue in the RRxxxR motif of PilZ domain by aspartic acid. This mutation in YcgR altered its ability to regulate T3SS expression. BcsA, another PilZ domain protein positively regulated T3SS. In chapter 4, we examined the role of Hfq in regulation of expression of T3SS. hfq mutant dramatically reduced the expression of T3SS genes such as, hrpA, hrpN and dspE. Hfq controlled T3SS expression by regulating expression of a response regulator, GacA which in turn regulates expression of rsmB. RsmB is an untranslated sRNA that positively regulates expression of the master regulator of the T3SS. hfq mutant also altered the expression of another sRNA, ArcZ that also regulated T3SS. Additionally, Hfq modulated the c-di-GMP levels in D. dadantii. Overall, the study suggested that Hfq regulated T3SS through Rsm system. The mechanism of Hfq regulating the c-di-GMP levels remains to be determined.
Keywords: C-di-GMP Receptor; Dickeya Dadantii; Erwinia Amylovora; HFQ; Small RNA; Type III Secretion System